2023
DOI: 10.1112/jlms.12778
|View full text |Cite
|
Sign up to set email alerts
|

Bertini theorems revisited

Abstract: We prove several new Bertini theorems over arbitrary fields and discrete valuation rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…We fix an embedding X ⊂ P N k and apply [20,Theorem 6.3] to find a hypersurface H ⊂ P N k such that the scheme-theoretic intersection Y = X ∩ H is normal and smooth along X o hypothesis from the famous Roitman torsion theorem [63]. Geisser [18] subsequently showed that the prime-to-p condition in the torsion theorem of Spieß and Szamuely could be eliminated if one assumed resolution of singularities.…”
Section: Relation With the Levine-weibel Chow Groupmentioning
confidence: 99%
“…We fix an embedding X ⊂ P N k and apply [20,Theorem 6.3] to find a hypersurface H ⊂ P N k such that the scheme-theoretic intersection Y = X ∩ H is normal and smooth along X o hypothesis from the famous Roitman torsion theorem [63]. Geisser [18] subsequently showed that the prime-to-p condition in the torsion theorem of Spieß and Szamuely could be eliminated if one assumed resolution of singularities.…”
Section: Relation With the Levine-weibel Chow Groupmentioning
confidence: 99%